Leadership in Computer-Mediated Communication: Implications and Research Directions - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2000)
Despite the importance of interpersonal influence processes in computer-mediated communication (CMC) environments, the emergence and functioning of leaders in CMC settings remains unstudied. An initial model and propositions address the possible extension of selected leadership models beyond face-to-face (FTF) communications and into the non-face-to-face CMC environment. We (1) model relevant variables for CMC leadership, (2) briefly review the implications of selected leadership models regarding these CMC variables, and (3) extend leadership models into the CMC sphere.